Drug-Induced Liver Injury: Biomarkers, Requirements, Candidates, and Validation - Meunier, Lucy; Larrey, Dominique (Frontiers in Pharmacology, 2019)
The hepatotoxicity of drugs is the main cause of drug withdrawal from the pharmaceutical market and interruption of the development of new molecules.Biomarkers are useful in several situations. In case of suspected DILI, biomarkers can be used to confirm liver damage, its severity, prognosis, confirm drug causality or define the type of DILI. In this review, we will first present the currently used biomarkers and candidate biomarkers for the future. The current biomarkers are certainly very helpful including with the assistance of diagnostic method such the RUCAM, but provide a limited information for the early dectection of liver injury, the role of specific drug and the prediction of DILI. Some biomarkers are promising but they are not yet available for routine use. Studies are still needed to confirm their interest, particularly in comparison to RUCAM.